ABC Transporters in Cancer Stem Cells: Beyond Chemoresistance. - Begicevic, R.; Falasca, Marco (MDPI AG, 2017)
The efficacy of chemotherapy is one of the main challenges in cancer treatment and one of the major obstacles to overcome in achieving lasting remission and a definitive cure in patients with cancer is the emergence of cancer resistance. Indeed, drug resistance is ultimately accountable for poor treatment outcomes and tumour relapse. There are various molecular mechanisms involved in multidrug resistance, such as the change in the activity of membrane transporters primarily belonging to the ATP binding cassette (ABC) transporter family. In addition, it has been proposed that this common feature could be attributed to a subpopulation of slow-cycling cancer stem cells (CSCs), endowed with enhanced tumorigenic potential and multidrug resistance. CSCs are characterized by the overexpression of specific surface markers that vary in different cancer cell types. Overexpression of ABC transporters has been reported in several cancers and more predominantly in CSCs. While the major focus on the role played by ABC transporters in cancer is polarized by their involvement in chemoresistance, emerging evidence supports a more active role of these proteins, in which they release specific bioactive molecules in the extracellular milieu. This review will outline our current understanding of the role played by ABC transporters in CSCs, how their expression is regulated and how they support the malignant metabolic phenotype. To summarize, we suggest that the increased expression of ABC transporters in CSCs may have precise functional roles and provide the opportunity to target, particularly these cells, by using specific ABC transporter inhibitors.